Answer:
K = 2
Explanation:
Simplifying
8(4k + -4) = -5k + 42
Reorder the terms:
8(-4 + 4k) = -5k + 42
(-4 * 8 + 4k * 8) = -5k + 42
(-32 + 32k) = -5k + 42
Reorder the terms:
-32 + 32k = 42 + -5k
Solving
-32 + 32k = 42 + -5k
Solving for variable 'k'.
Move all terms containing k to the left, all other terms to the right.
Add '5k' to each side of the equation.
-32 + 32k + 5k = 42 + -5k + 5k
Combine like terms: 32k + 5k = 37k
-32 + 37k = 42 + -5k + 5k
Combine like terms: -5k + 5k = 0
-32 + 37k = 42 + 0
-32 + 37k = 42
Add '32' to each side of the equation.
-32 + 32 + 37k = 42 + 32
Combine like terms: -32 + 32 = 0
0 + 37k = 42 + 32
37k = 42 + 32
Combine like terms: 42 + 32 = 74
37k = 74
Divide each side by '37'.
k = 2
Simplifying
k = 2